Електрофізичні властивості системи поліхлортрифторетилен/йодид міді - Mazurenko, R. V.; Makhno, S. N.; Gorbyk, P. P. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2011)
Dependences of dielectric complex permittivity and conductivity of composites based on polychlortrifluoroethylene on content CuI in field of low (0,1–10 kHz) and ultrahigh (8–12 GHz) frequencies were investigated. A new technique of fabrication polymer composites materials (PCM) is proposed based on surface modification of polymer by dispersed conductive components. Analysis of the experimental data shows that proposed technique has a high efficiency of produce PCM with enhanced exploitation parameters and wider adjustment range of electrophysical properties.